Effect of fats and ionophores on in vitro fermentation of a high concentrate diet - E.M. Clary; Robert T. Brandt Jr.; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1990)
Batch culture fermentations were used to determine the effects of fat type [none, animal tallow (AT), soybean oil soapstock (SOY), or yellow grease (YG)] and ionophore type [none, lasalocid (L), monensin + tylosin in a ratio of 2.5:1 (MT), or a 50:50 combination of Land MT (LMT)] on in vitro concentrations of lactate (LA) and volatile fatty acids (VFA). Fat-containing substrates had 4% fat on a dry basis. No significant interactions between fat and ionophore treatments were observed. Ionophore treatment resulted in a reduced pH, with the greatest reduction in the L treatment. lbtal VFA and LA increased with ionophore treatment and were highest with L treatment. All ionophore treatments decreased molar proportions of acetate and butyrate and increased propionate. Lasalocid produced a lower molar proportion of acetate and a higher molar proportion of propionate than did MT. Adding fat resulted in a reduction in total VFA and an increase in pH. The reduction in total VFA was less for SOY than AT or YG treatments. No significant differences in LA or VFA molar proportions were observed among fat treatments. Our results indicate that the rate of starch digestion may be slowed by fat, which may translate into a decreased incidence of ruminal acidosis.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Fats; Ionophores; Fermentation; Volatile fatty acids; Lactic acid